PERTANGGUNGJAWABAN PIDANA PEGAWAI PENGADILAN NEGERI DALAM TINDAK PIDANA KORUPSI - Kombat Germado; Musmuliadin Musmuliadin; Zuhrah Zuhrah (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2026)
Corruption in the judiciary is one of the most destructive manifestations of official crimes, as it directly undermines public trust in institutions that should be the last bastion of justice. District court employees, as officials who have access to case documents, judicial administration processes, and communication between litigants, are in a vulnerable and strategic position in the ecosystem of judicial corruption. This study aims to comprehensively analyze the criminal liability framework for district court employees involved in corruption, identify normative gaps in existing regulations, and formulate recommendations for legal reforms that are adaptive to the development of contemporary judicial corruption modus operandi. The method used is normative legal research with a statutory approach, a conceptual approach, and a comparative approach, supported by an analysis of jurisprudential cases of the Supreme Court and the Corruption Eradication Commission (KPK) in the 2015–2024 period. The results of the study indicate that the criminal liability of district court employees in corruption crimes is subject to Law Number 31 of 1999 in conjunction with ... Law Number 20 of 2001 concerning the Eradication of Criminal Acts of Corruption, however, there are a number of normative disharmonies between these provisions and Law Number 5 of 2014 concerning State Civil Apparatus and Law Number 48 of 2009 concerning Judicial Power. This research is novel in integrating the analysis of the doctrine of criminal liability with the institutional design of the judiciary and recommends the establishment of an internal anti-corruption protocol specifically for the court environment. Keywords: Criminal Liability; District Court Employees; Corruption; Judicial Corruption; Legal Reform.